Differences in Weight Gain between 1 Month Injection Contraceptive and 3 Month Injection Contraceptive Acceptors at Delta Mutiara Maternity Clinic. - Syubah, Afinatus; Kusumawardani, Paramitha Amelia; Cholifah, Siti (Jurnal MIDPRO, 2024)
The high birth rate is still a major problem in Indonesia’s population which until now has not been able to be overcome. Injectable contraception is a way to prevent pregnancy through hormonal injections. There are 2 types of injectable birth control, namely 1-month injection and 3-month injection. Weight gain is the highest side effect of injecting contraception which is the body's adjustment to hormonal changes so that the possibility of weight gain occurring does not last long. The purpose of this study was to determine differences in weight gain in 1-month and 3-month injection contraceptive acceptors at the Delta Mutiara Maternity Clinic. The method used quantitative analysis with a cross-sectional design and this research used a quota sampling technique, data processing was carried out in 2 ways, univariate analysis to describe the characteristics of each variable and bivariate analysis using an Independent T Test with an error rate of 5% (0.05). The results showed that the significant value for 1-month injection contraceptive acceptors was p=0.004 (p=>0.05) and 3-month injection contraceptive acceptors obtained a significant value of p=0.000 (p>0.05). There was a significant difference in weight gain in 1-month and 3-month injection contraceptive acceptors at the Delta Mutiara Maternity Clinic.